2020
DOI: 10.3390/biom10091246
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization of Biomembrane Assemblies

Abstract: While atomic scale structural and dynamic information are hallmarks of nuclear magnetic resonance (NMR) methodologies, sensitivity is a fundamental limitation in NMR studies. Fully exploiting NMR capabilities to study membrane proteins is further hampered by their dilution within biological membranes. Recent developments in dynamic nuclear polarization (DNP), which can transfer the relatively high polarization of unpaired electrons to nuclear spins, show promise for overcoming the sensitivity bottleneck and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 115 publications
0
12
0
Order By: Relevance
“…This forms homogeneous MLVs which are then pelleted by ultracentrifugation. Following this, PA and cryoprotectant are added, the sample is subjected to additional freeze–thaw cycles (×15), and finally the MLVs are directly centrifuged into the MAS rotor …”
Section: Sample Constitution For Biomolecular Dnpmentioning
confidence: 99%
“…This forms homogeneous MLVs which are then pelleted by ultracentrifugation. Following this, PA and cryoprotectant are added, the sample is subjected to additional freeze–thaw cycles (×15), and finally the MLVs are directly centrifuged into the MAS rotor …”
Section: Sample Constitution For Biomolecular Dnpmentioning
confidence: 99%
“…Magic angle spinning (MAS) solid-state NMR is not limited by molecular correlation times and is particularly useful to study large protein complexes, amyloid fibrils, and membrane proteins. With the sensitivity gains conferred by dynamic nuclear polarization (DNP), MAS NMR has the sensitivity to detect proteins at their endogenous concentrations in complex biological environments. ,,, However, the effectiveness of DNP-enhanced MAS NMR is critically dependent on sample composition and experimental conditions. , DNP increases the sensitivity of NMR spectroscopy through the transfer of the large spin polarization of an unpaired electron to nearby nuclei which are typically introduced into a sample by doping with millimolar concentrations of stable biological radicals. In addition to millimolar concentrations of polarizing agents, a typical DNP sample of a hydrated biomolecule is cryoprotected by the addition of 60% d 8 -glycerol to aid in the formation of vitreous ice, deuterated to ∼90% to aid spin diffusion, frozen to near liquid nitrogen temperatures, and subjected to magic angle spinning. Pioneering work applying DNP MAS NMR to cultured mammalian cells suggested that measurement of low concentrations of proteins inside mammalian cells is possible, but uncertainty about the biological integrity of the cellular sample limits the utility of the structural information for in-cell experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR (SSNMR) is essential to the structural and functional characterization of membrane proteins (MPs) ( Schubeis et al, 2018 ; Radoicic et al, 2014 ; Wylie et al, 2016 ; Mandala et al, 2018 ; Tran et al, 2020 ). SSNMR can study MPs in native or native-like environments, allowing site-specific analysis of protein structure and activity.…”
Section: Introductionmentioning
confidence: 99%